Yoga from the inside out : making peace with your body through yoga - Sell, Christina (New Delhi : Third Eye, 2004)
There are dozens of books that tell you where to place your heel when you do yoga, where to put your arm, how to bend your waist...This is a book that teaches where to place your heart when you do yoga. There is more to yoga than postures, and Christina Sell draws on her own experience and that of her students to produce the first book on Anusara Yoga. A beautiful book about women in yoga, finding peace and acceptance and bringing that to their lives, their bodies and their practice.
Includes index.
Keywords: Hatha yoga; Body image; Yoga -- Therapeutic use